(untitled) (Marketing Journal, 2025)
This scientific article explores the ongoing reforms in the electric power network, their outcomes, and the persistent challenges in the sector. It analyzes the natural monopoly conditions in the production and transmission of electricity, as well as issue s in regulation and management of the energy industry. Based on the findings, the paper offers recommendations and practical solutions to address these challenges.